Evaluation of the in vitro and in vivo efficacy of ruthenium polypyridyl compounds against breast cancer - Lenis‐rojas, Oscar A. (2022)
Project ED431C 2018/39 PEst 20152020 UID/QUI/00100/2020 UIDP/04378/2020 UIDB/04378/2020 LA/P/0140/2020